Regional ADC values of the morphologically normal canine brain - Carisch, Lea; Lindt, Blanca; Richter, Henning; Del Chicca, Francesca (Frontiers in Veterinary Science, 2023)
Introduction Diffusion-weighted magnetic resonance imaging is increasingly available for investigation of canine brain diseases. Apparent diffusion coefficients (ADC) of normal canine brains are reported only in small numbers of subjects. The aim of the study was to investigate the ADC of different anatomical regions in the morphologically normal brain in a large population of canine patients in clinical setting. Additionally, possible influence on the ADC value of patient-related factors like sex, age and body weight, difference between the left and right side of the cerebral hemispheres, and between gray and white matter were investigated.Methods Brain magnetic resonance studies including diffusion-weighted images of dogs presented at the Vetsuisse Faculty-University Zurich between 2015 and 2020 were reviewed retrospectively. Only morphologically normal brain magnetic resonance studies of dogs presented with neurological signs or non neurological signs were included. ADC values of 12 regions of interest (ROIs) in each hemisphere and an additional region in the cerebellar vermis were examined in each dog.Results A total of 321 dogs (including 247 dogs with neurological signs and 62 dogs with non neurological signs) of various breeds, sex and age were represented. ADC significantly varied among most anatomical brain regions. Significantly higher ADC was measured in the gray (median 0.79 (range 0.69 -0.90) x10 -3 mm 2 /s) compared to the white matter (median 0.70 (range 0.63 -0.85) x10 -3 mm 2 /s). No significant differences were found between the left and right cerebral hemispheres in most of the regions, neither between sexes, different reproductive status, and body-weight groups. Age was correlated first with a decrease from dogs <1 year of age to middle-age (⩾3 to <8 years) dogs and later with an increase of ADC values in dogs ⩾8 years.Discussion ADC values of 25 ROIs were described in 321 morphologically normal canine brains in clinical setting. ADC differences depending on the brain anatomical region are present. ADC differences among age classes are present, likely consistent with brain maturation and aging. The described data can be a reference for future studies in clinical settings on the canine brain.